Creativity—the unconscious foundations of the incubation period - Ritter, Simone M.; Dijksterhuis, Ap (Frontiers in Human Neuroscience, 2014)
Creativity is one of the most important assets we have to navigate through the fast changing world of the 21st century. Anecdotal accounts of creative individuals suggest that oftentimes, creative discoveries result from a process whereby initial conscious thought is followed by a period during which one refrains from task-related conscious thought. For example, one may spend an embarrassing amount of time thinking about a problem when the solution suddenly pops into consciousness while taking a shower. Not only creative individuals but also traditional theories of creativity have put a lot of emphasis on this incubation stage in creative thinking. The aim of the present article is twofold. First, an overview of the domain of incubation and creativity is provided by reviewing and discussing studies on incubation, mind-wandering, and sleep. Second, the causes of incubation effects are discussed. Previously, little attention has been paid to the causes of incubation effects and most findings do not really speak to whether the effects should be explained by unconscious processes or merely by consequences of a period of distraction. In the latter case, there is no need to assume active unconscious processes. The findings discussed in the current article support the idea that it is not merely the absence of conscious thought that drives incubation effects, but that during an incubation period unconscious processes contribute to creative thinking. Finally, practical implications and directions for future research will be discussed.